Magnesium in hypertension: mechanisms and clinical implications - AlShanableh, Zain; Ray, Evan C. (Frontiers in Physiology, 2024)
Hypertension is associated with increased risk of cardiovascular disease and death. Evidence suggests that Mg 2+ depletion contributes to hypertension. It is estimated that 25% or more of the United States population experiences chronic, latent Mg 2+ depletion. This review explores mechanisms by which Mg 2+ influences blood pressure, modifying risk of hypertension and complicating its treatment. Mechanisms addressed include effects upon i) sympathetic tone, via the modulation of N-methyl-D-aspartate (NMDA) receptor and N-type Ca 2+ channel activity, influencing catecholamine release from sympathetic nerve endings; ii) vascular tone, via alteration of L-type Ca 2+ and endothelial nitric oxide synthase (eNOS) activity and prostacyclin release; iii) renal K + handling, influencing systemic K + balance and potentially indirectly influencing blood pressure; iv) aldosterone secretion from the adrenal cortex; and v) modulation of pro-hypertensive inflammatory processes in dendritic cells and macrophages, including activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome and stimulation of isolevuglandin (IsoLG) production. Discovery of these mechanisms has furthered our understanding of the pathogenesis of hypertension, with implications for treatment and has highlighted the role of Mg 2+ balance in hypertension and cardiovascular disease.